Effect of surface treatment on microstructure of ferroelectric glass-ceramics containing NN and BNN. (2019) - Tipakontitikul, R.; Niyompan, A.
Abstract: Ferroelectric properties of the glass-ceramics are correlated with the active crystals and the glass matrix which may exhibit complicated dielectric respond. It is interesting to find a method that can reduce the effect of glass matrix. The attempt of this work is to use surface treatment method. Glass-ceramic samples with and without Nd 3+ doping were employed for the surface treatment process. After treatment by submersing glass-ceramic specimens into the diluted HF solution, phase variation and microstructural development of the samples were checked. XRD results of the treated glass-ceramic revealed a portion dissolution of NN and BNN to form sodium fluorosilicate (Na2 SiF6 ) and barium fluorosilicate (BaSiF6 ). This observation is more pronounced in the sample with Nd 3+ doping. Formations of the fluorosilicate type crystals indicate that F - reacted not only with [SiO4 ] 4- silicate units in the glass matrix but also with the main crystalline phases. These observations are confirmed by SEM micrographs. Microstructural developments are clearly seen as the growths of the rod shape of sodium fluorosilicate and barium fluorosilicate crystallites.